Hubungan Hukum Dalam Penerapan Bank Secrecy Law Pada Nasabah Penyimpan Dana dan Lembaga Perbankan - Setyamika, Bunga; Sutrisno, Sutrisno (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2025)
This research aims to examine the legal relationship between Bank and customers who save funds from the aspects of contracts, confidentiality obligations and the bank's responsibilities towards customers who experience account breaches. The research method used is normative juridical, carried out by literature study. Data collection was carried out by research through books, statutory regulations and published journals. Based on the research results, it was found that the legal relationship between banks and depositors is based on the principle of trust between both parties. The relationship between banking institutions and deposit customers uses a lending and borrowing contract in accordance with Article 1754 of the Civil Code. Regarding the bank's responsibility to provide compensation in the form of a refund of funds or similar goods or services whose value is equal.